Beyond the Chilly Chariots: A Contemplation of Nothingness in Wallace Stevens' Harmonium - Elias Naqipour; Ali Taghizadeh; Pedram Lalbakhsh (Critical Literary Studies)
This paper deals with Wallace Stevens’s first collection of poetry, Harmonium, in light of Heidegger’s philosophy, with a particular emphasis on Da-sein as the place of negativity. The focus is particularly on Heidegger’s later philosophy, where he defines Man as the juncture where the four constitutive elements (earth, sky, divinities, and mortals) converge to let Da-sein appear as the futural authentic animal whose Being matters to him as his distinctive mark. Stevens’s poetry in Harmonium displays an experimental development along the same lines. The collection consists of poems dealing with the effect that the prospects of death and finitude have on its protagonists. Stevens achieves authentic protagonists who accept the nihilating power of death in order to save themselves from any form of social, poetic, and philosophical closure. This is significant because Stevens conceives a creative potential that not only runs counter to the romantic nostalgia for a return to an innocent past, but also openly embraces the idea of finitude as the only way out of any logocentric and metaphysical forms of thinking. This study, therefore, aims to show how in Harmonium Stevens poetizes an endless creative power that sets upon reproducing the non-closure associated with nihilation and nothingness.